PS 17-30 FACTORS DETERMINING EXERCISE CAPACITY IN COMMUNITY-DWELLING APPARENTLY HEALTHY SUBJECTS. (September 2016) - Jung, Mi-Hyang; Ihm, Sang-Hyun; Lee, Dong-Hyeon; Park, Ha-Wook; Choi, Young; Chung, Woo-Baek; Jung, Hae Ok; Youn, Ho-Joong
Abstract : Objective: The peak VO2 is a well validated representative of exercise capacity. Its prognostic implication has been tested in various pathologic conditions, such as heart failure and pulmonary hypertension. However, the determinant of the exercise capacity in apparently healthy subject is unclear. Design and method: From January 2011 to May 2013, a total of 382 asymptomatic subjects (mean age 53 ± 9 years, females 36.9%) without a previous history of hypertension were retrospectively analyzed. Eligible participants were those who underwent comprehensive health check-ups, including cardiopulmonary exercise tests, echocardiography, and InBody 720 analyses. Results: The participants had a mean systolic and diastolic blood pressure of 120.2 ± 11.1 and 72.2 ± 8.4 mmHg, respectively. The participants had mild obesity (mean body mass index 24.4 ± 3.2 kg/m2). The peak VO2 was positively associated with the muscle mass (r = 0.412, p < 0.001) and negatively associated with the age (r = −0.313, p < 0.001), E/e' (r = 0.274, p < 0.001) and fat mass (r = −0.230, p < 0.001, Figure 1). However, the values of the blood pressure, ejection faction, fasting blood glucose level, HOMA-IR, and lipid profile were not associated with the peak VO2 . A multivariate linear regression analysis demonstrated that the age ( ß = −0.142, p < 0.001), muscle mass ( ß = 0.429, p < 0.001), and fat mass ( ß = −0.361, p < 0.001) were independent determinants of the exercise capacity. Conclusions: Our observations demonstrated that the exercise capacity is mainly determined by the age and peripheral factors, such as the muscle and fat mass, in apparently healthy subjects.